In vitro cultures of Curcuma mangga Val. for the production of (E)-labda-8(17), 12-diene-15, 16-dial / Tamil Chelvan Meenakshi Sundram - Meenakshi Sundram, Tamil Chelvan (2012)
Curcuma mangga Val., commonly known as the mango ginger has been used traditionally as a seasoning for food and as a treatment for stomach aches, fever, and cancer. Due to its medicinal importance, a systematic approach was taken to establish a rapidly growing suspension culture of C. mangga. In initiating callus, various responses were obtained from shoot bud explants cultured on MS basal medium supplemented with different concentrations of 2,4-D, NAA and IAA either alone or in combinations. Different concentrations of sucrose were also tested. Rapid growing friable callusobtained from shoot explants cultured on MS basal medium supplemented with 1 mg l-1 2,4-D, 30 g l-1 sucrose and 2 g l-1 gelrite were selected for the initiation of suspension cultures based on histological morphology. From various medium screened, rapid growing suspension cultures were established by using MS liquid medium supplemented with 0.3 mg l-1 2,4-D, 0.1 mg l-1 NAA, 30 g l-1 sucrose, 0.1 g l-1 malt extract, 0.5 mg l-1 d-Biotin, 100 mg l-1 glutamine, 5 mg l-1 ascorbic acid and citric acid respectively. Phenolic compounds production was most effectively controlled by the incorporation of ascorbic and citric acid as antioxidants. (E)-labda-8(17),12-dien-15,16 dial is one of the bioactive compounds isolated from rhizomes of C. mangga. Recently, the cytotoxicity of this compound against cancer cells has been reported. (E)-Labda-8(17),12-dien-15,16 dial was extracted from cells, callus, rhizomes and shoots using solvent extraction method. Gas Chromatography (GC) and Gas Chromatography Flame Ionization Detector (GCFID) was used to compare the quantity of (E)-labda-8(17),12-dien-15,16 dial production in suspension cells and callus induced through various treatment and at different growth period.The presence of this compound in field grown rhizomes and in vivo shoot buds samples were also tested. The amount of (E)-labda-8(17),12-dien-15,16 dial in in vivo sources was higher than the in vitro sources, but the presence can be enhanced through various method in future studies.